1991
DOI: 10.1104/pp.96.1.50
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Glycerol Synthesis in Response to Osmotic Changes in Dunaliella

Abstract: Changes in phosphometabolites, following osmotic shock, were analyzed by two-dimensional thin layer chromatography, in extracts of the halotolerant alga DunalielIa salina in order to clarify the regulation of glycerol synthesis from starch. The experiments were carried out in wild-type and in osmotically defective mutant cells. It is demonstrated that hyperosmotic shock induces a decrease in fructose 6-phosphate and an increase in fructose-1,6-bisphosphate indicating the activation of phosphofructokinase. Two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(55 citation statements)
references
References 21 publications
1
54
0
Order By: Relevance
“…The appearance of phosphocholine in D. salina is likely to have physiological significance because osmotic shock does not decrease the surface area of the plasma membrane (6) and phosphocholine accumulation is not observed in osmotically defective mutants that have very slow glycerol synthesis (4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The appearance of phosphocholine in D. salina is likely to have physiological significance because osmotic shock does not decrease the surface area of the plasma membrane (6) and phosphocholine accumulation is not observed in osmotically defective mutants that have very slow glycerol synthesis (4).…”
Section: Discussionmentioning
confidence: 99%
“…In mammalian cells, PtdCho breakdown products (DAG and phosphatidic acid) have been implicated in agonist-induced signal transduction (7,17). Chitlaru and Pick (4) suggested that signal transduction involving PtdCho hydrolysis may be important in osmoregulation in Dunaliella, and it is possible that this pathway could exist in the system studied here. However, these processes are usually thought to involve low concentrations of messengers and to occur on a time scale of minutes, although Cabot et al (2) observed phorbol-induced release of choline metabolites during a period of 2 h. Hence, it is not possible to obtain information about these processes from the experiments described here.…”
mentioning
confidence: 89%
“…: 0.5/g) and the second dimension with n-butanol/n-propanol/npropionic acid/H 2 O (400:175:285 :373, by vol.) [24,25].…”
Section: Methodsmentioning
confidence: 99%
“…Unlabeled spots were detected by exposing the TLC plates to ninhydrin reagent, (amine-containing metabolites), ultraviolet light (nucleotides), or iodine vapor (lipids). Phosphates on poly(ethylimine) cellulose plates (which had been washed with absolute methanol and dried) and cellulose TLC plates were detected by spraying with phosphomolybdate reagent [25] and then heated (85°C for Ϸ10 min). For quantitative autoradiographic analysis of radioactive spots, the TLC plates were imaged in a FUJI-X Bio-imaging analyzer (BAS1000 MacBas, Fuji Photo Film Co., Ltd), and the results were quantitated after subtracting background values.…”
Section: Methodsmentioning
confidence: 99%
“…Volvox carteri, a multicellular microalga, is another well-established model species for the elucidation of the genetic basis of cellular differentiation (Miller, 2002). In recent years, the green alga Dunaliella salina has been utilized to complement the study of photosynthesis, osmoregulation, carotenogenesis, and glycerol production (Jin et al, 2001;Liska et al, 2004;Thompson, 2005;Shaish et al, 1992;Chitlaru et al, 1991). Dunaliella salina is an attractive platform for both commercial and academic pursuits owing to its intriguing and advantageous abilities to survive in conditions of extreme salinity and produce significant amounts of -carotene.…”
Section: Toward the Development Of Selectable Markers For Dunaliella mentioning
confidence: 99%